DETERMINANTS OF CHANGES IN THE INCOME LEVEL OF MSME ACTORS IN PAHLAWAN VILLAGE, BATUBARA DISTRICT - Rahmad Sembiring; Uswatun Hasanah; Anggia Ramadhan (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to analyze how the income of MSME traders during the Covid-19 Pandemic is approximately what factors affect the income of MSME traders. This research was conducted using quantitative research methods using CFA (Confirmatory Factor Analysis) and Multiple Linear Regression. Data collection techniques in this study were in the form of interviews, questionnaires and documentation, and the data used were primary data. The results of the study using show that the factors that affect the income of MSME traders, namely the Old Business Factor (X1), Capital (X2), and the Use of Technology (X3) and Income (Y), of these three factors the Old Business Variable does not have a significant effect on the income of MSME traders shown by the Sig. X1 to Y is 0.284 > 0.05 and t count 1.083 < t table 2.006 so it can be concluded that H1 is rejected which means there is no effect of Business Length (X1) on MSME Merchant Income (Y ), furthermore, the Capital Variable has a significant effect on the income of MSME traders which is indicated by the Sig. X2 to Y is 0.004 < 0.05 and t count 3,051> t table 2,006 so it can be concluded that H2 is accepted which means that there is an influence of Capital (X2) on Income (Y) and also Variables The use of Technology has a significant effect on the income of MSME traders as indicated by the value of Sig. X3 to Income (Y) is 0.029 < 0.05 and t count 2,240 > t table 2.006 so it can be concluded that H3 is accepted which means that there is an effect of Technology Use (X3) on Income (Y). The conclusion is that the Business Duration does not have a significant effect on the income of MSME traders, while capital and the use of technology have a significant effect on the income of MSME traders. Traders should pay more attention to factors that affect income in order to increase the income of MSME traders.